Avaliação da atividade neuroprotetora do extrato padronizado de Camellia sinensis e de seus princípios bioativos: envolvimento de ações anti-inflamatórias e antioxidantes - Pinto, Natália Bitú (2015)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by destruction of nigrostriatal dopaminergic neurons. Current treatment is only symptomatic and, to date, there are no drugs capable of inhibiting neuronal degeneration. So great is the demand for neuroprotective agents to prevent or slow the progression of this disease. The Camellia sinensis is a species of the family Theaceae, popularly known as green tea (CV). Several studies have shown the beneficial effects of this plant and its bioactive principles against neurodegenerative diseases. The objective of this study was to evaluate the neuroprotective effect of standardized extract of green tea and its catechins, epicatechin (EC) and epigallocatechin 3-gallate (EGCG), the PD model induced by 6-OHDA in rats, as well as studying the CV effect in models of inflammation and nociception. The animals (male Wistar rats, 180-250 g) were treated orally with HP (25 or 50 mg / kg), catechins (EC and EGCG at a dose of 10 mg / kg), the combination of CV (25mg / kg) + L-DOPA (25 mg / kg) with L-DOPA alone (at doses of 25 or 50 mg / kg) for 14 consecutive days; the treatments were started 1 hour before the unilateral striatal lesion by 6-OHDA (24 mg / 2μL). In behavioral tests, the results showed a significant increase in the number of rotations induced by apomorphine, decreased locomotor activity in the open field test, increased immobility time in the test in forced swimming, increased platform against time in the test water maze and increased the number of falls in the route of the test rod in the injured animals with 6-OHDA, compared to false-operated animals. These changes were partly or fully reversed after treatment with CV, CV + L-DOPA, EC, EGCG and L-DOPA alone. The 6-OHDA triggered neuronal death, as shown by reduced levels of dopamine and metabolites (DOPAC and HVA) in the striatum lesioned right compared to non-lesioned striatum left (contralateral). This depletion was significantly attenuated in injured and treated with CV, L-DOPA, EC, EGCG and association CV 25 25 + L-DOPA; these same drugs decreased levels of TBARS (indicator of lipid peroxidation) and nitrite / nitrate (oxidative stress indicator) in the striatum of rats with striatal injury by 6-OHDA. In vitro experiments have shown that CV (0.1-100 ug / uL) showed a strong antioxidant effect, by reducing the production of oxidizing substances in human neutrophils stimulated by PMA. In Nissl staining, it was observed that the injured animals and treated with CV, and CV EGCG + L-DOPA there was preservation of hippocampal neurons. Treatment with CV and CV + L-DOPA increased immunoreactivity for TH and decreased immunostaining for COX-2 in the striatum as well as the CV and EGCG attenuated the markup for iNOS in the hippocampus of treated animals compared to the control group. It was observed that the CV potentiate the effect of L-DOPA, showing a possible synergistic effect between these drugs. In another stage of the study, we evaluated the anti-inflammatory / nociceptive CV. Thus, the paw edema model induced by carrageenin and dextran, there was a decrease in volume of paw edema of rats after treatment with VC, compared to the control group (treated only with distilled water). The CV produced antinociceptive effect in the formalin test and the writhing induced by acetic acid, but also in the hot plate test and Hargreaves, possibly through the activation of opioid receptors and reducing the inflammatory process. In these tests nociception and inflammation, the CV potentiate the effects of morphine, indomethacin and dexamethasone. Therefore, our results demonstrated the neuroprotective effects of the CV and its bioactive principles, EC and EGCG, probably due to its anti-inflammatory and antioxidant properties, making future therapeutic options for the prevention or treatment of neurodegenerative diseases such as disease Parkinson.